Constructive features of rotary furnaces - S. L. Rovin; L. E. Rovin (Литьë и металлургия)
The article deals with the design of rotary tilted melting furnaces (RTF), modeling of operation and calculation of the most loaded components and structural elements of these units. The results of the development and analysis of the operating experience of RTF used for processing various dispersed materials are presented. Recommendations for choosing optimal design solutions for rotary furnaces for recycling dispersed metal waste are given.